In-migration as a new process in demographic problem areas of the Alps. Ghost towns vs. amenity settlements in the alpine border area between Italy and Slovenia - Steinicke, Ernst; Cede, Peter; Löffler, Roland (ERDKUNDE, 2012)
Even recent academic studies consider the Italian Alps (with the exception of South Tyrol) still a huge out-migration and depopulation area. The present contribution, however, shows the new and remarkable phenomenon of in-migration. The study highlights the west-east difference in regard to the significance of the newcomers for the current structural change in peripheral Alpine regions: ensuing from the demographic turnaround in the French Alps starting in the mid-1980s, the process of amenity migration spread across the Italian Alps. The present study seeks to analyze its outcomes through a comparison of the Alpine border areas between Italy and Slovenia. The eastern part of the Friulian mountain region, particularly the border areas toward Slovenia, suffered the heaviest population losses in the Alps between WWII and 1990. It is therefore not surprising that here traditional spatial structures still continue to exist and in contrast to other demographic problem areas in the Italian Alps, e.g. the Cottian Alps, the population development has remained largely negative, though in the meantime the phenomenon of amenity migration has reached these Friulian communities. The west-east proliferation of amenity migration has also extended onto the Slovenian side, but its effects are less apparent due to the weaker depopulation processes during the period of the Yugoslavian regime. Regardless, the overall demographic reversal proclaims itself unmistakably and the resettlement of the once completely abandoned villages is a significant indicator for this tendency.